Food security in Africa and Asia [ strategies for small-scale agricultural development - Bakker, H. [ (Henk)] , 1926- (CABI, 2011)
This book builds on the premise that food security in low-income countries may be achieved through sustained effort by the local small-scale and subsistence farming communities, with the active support from local, national and international agencies. Itstates that any such effort will endure only if those small-scale farming communities and subsistence farmers feel that their interests are protected. Therefore, those local communities should be involved in the process of working towards sustainable food security to the extent that they consider that they 'own' the project designed for that purpose. To achieve this, such a project should be based on the concept of participatory action and learning. Therefore, the book is directed towards policy makers of local, national and international organizations and agencies which are prepared to listen, learn from and work with local farmers and their representatives. The book has 10 chapters.